Analysis of the Concept of Force Balance in the Atag Warehouse, Jember Regency - Vestnanda, Alfrida Diftia; Handayani, Rif'ati Dina; Lesmono, Albertus Djoko (Universitas Negeri Surabaya, 2023)
Physics learning is rarely associated with the local wisdom of the local community, so most people assume that the two topics are very different. This article analyzes the concept of force balance in the Atag warehouse building in Jember Regency. This study used qualitative research using content analysis techniques in which there is unitizing, sampling, coding, reducing, inferring, and narrating. Data were collected through field observations, literature studies, interviews, and documentation. The research indicates that the Atag warehouse building has several parts, namely doors, windows (tabing lambung), columns (rooms), warehouse roofs, and foundations. In the Atag warehouse, there is the concept of static balance, namely the equilibrium of rigid objects found in the frame, rope ties, foundation, semat, and Atag warehouse doors. Then there is the concept of a heavy point found in the bottom cover and the center of the Atag shed. Furthermore, there is the concept of dynamic balance, namely the moment of force that can be found in the warehouse window and the moment of inertia in the bamboo part whose bonds loosen when stepped on by warehouse workers. Integrating Atag warehouses in learning activities can make it easier for students to understand physics concepts. This article concludes that the Atag warehouse has a static and dynamic balance that can be used as physics learning material and can also help preserve regional culture.